(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents a thorough investigation into the integration of STEM (Science, Technology, Engineering, and Mathematics) technologies in primary education, focusing on both the current experience of Uzbekistan and broader international trends. Drawing from empirical research, policy analysis, and comparative studies, the paper examines how robotics, coding, hands-on projects, and digital platforms impact students’ academic performance, problem-solving skills, and engagement from an early age. Results indicate that students in STEM-enriched environments achieve significantly higher gains in mathematics, science, and computational thinking, with special progress among girls and students in rural schools due to targeted inclusion strategies. Challenges related to infrastructure, teacher capacity, and localized curriculum remain, but sustained investment, professional development, and cross-sector collaboration have already shown promising outcomes. The study concludes with practical recommendations for policymakers and educators to ensure all children, regardless of background, have access to quality STEM education that prepares them for the demands of the digital future.